Peran Akuntan Dengan Kompetensi Teknologi Informasi Pada UMKM Di Era Globalisasi - Novianti Indah Putri; Mira Ismirani Fudsy; Dedi Karmana; Sakti Muda Nasution; Zen Munawar; Budi Lesmana (LPPM POLITEKNIK LP3I BANDUNG, 2022)
The development of information technology demands a change in the role of accountants, which was originally only a provider of information, increasing in the role of decision makers. There are big challenges in the era of globalization such as changing patterns of competition in the business world and the development of information technology, this requires the role of accountants to be more proactive in managing the economy and finances. The key to success in facing competition in the era of globalization is the ability to innovate, adapt and implement information technology. By waging war on the possibility of obstacles and the ability to make solutions, accountants with information technology competence become an important profession in organizations. From the results of this thought, this research focuses on the function and role of accountants in micro, small and medium enterprises which ultimately contribute to the organization, and as business partners in the organization where the accountant is located.